Islamic Education in a Multicultural Society: The Case of a Muslim School in Canada - Ali, Faisal Mohamed; Bagley, Carl (Canadian Journal of Education/Revue canadienne de l’éducation, 2015)
The case study explores the ways in which a prominent, private Canadian Muslim school provides an Islamic education while negotiating its place in an integrated, socially cohesive, multicultural society. The data are derived from an in-depth qualitative investigation utilizing documentary analysis, participant observation, and interviews (N = 22). The findings reveal the ways in which the school perceives the specific challenges in negotiating the tension between their aspiration to preserve Islamic values and wider socio-political pressures to integrate into Canada’s multicultural society. The study concludes that both the nature of Islamic educational provision and Canadian multicultural policy require modification and change.